(untitled) (Jurnal Teknologi (Sciences & Engineering), 2021)
The pH-dependent structures of the bovine serum albumin (BSA), under physiological conditions that permit enzymatic activity, were investigated by small-angle neutron scattering (SANS). The unfolding behavior of BSA in solution is important to understand the mechanism of protein aggregation due to protein conformational change. The information of protein structure is crucial to design the perfect protein-based drug delivery device. This information will be useful as a complementary data of BSA crystal structure in static state. The structure of BSA in solution was found to be heart shaped, nearly identical to bovine serum albumin crystal structure. The globular heart shaped structure of BSA was still maintained at alkaline pH range of 7 to 11. It underwent partial unfolding at pH 5 and continued to unfold at pH 3. The unfolded-structure of BSA shows that the globular structure started to change into a cylinder-like structure at pH 3 which was clearly shown in Kratky plot. These results were confirmed with ab initio low-resolution shape calculation model analysis using GNOM and DAMMIF in obtaining the three-dimensional protein structure model.